Influence of the transom immersion to ship resistance components at low and medium speeds (Journal of Naval Architecture and Marine Engineering, 2020)
The transom stern offered some advantages over the traditional rounded cruiser stern reducing the resistance of a ship. This can only be achieved if the transom stern is carefully designed with suitable transom immersion ratio. In this study, the influence of different transom area immersion ratios on the resistance components was investigated for a semi-displacement hull and a full displacement hull.  The base hull was based on NPL hull form and KCS hull form for a semi-displacement and full-displacement hull respectively. The transom immersion ratios for the NPL hull were varied at a ratio of 0.5, 0.7, 0.8 and 1.0.  The resistance of each of the NPL hull form was simulated at Froude number 0.3 up to 0.6. The transom immersion ratios for the KCS hull were varied at a ratio of 0.05, 0.1, 0.15 and 0.3. The resistance of each of the KCS hull form was simulated at Froude number 0.195, 0.23, 0.26 and 0.28.  The transoms of both hulls were modified or varied systematically to study the influence of the transom shape or immersion on the total and wave resistance components. The investigation was carried out using a CFD software named SHIPFLOW 6.3 based on RANSE solver. These results on the NPL hull shows that the larger the transom immersion, the higher the resistance will be for a semi-displacement vessel. The increased resistance is contributed by additional frictional and wave resistance components. The results for the KCS hull seems to contradict with the results obtained from the NPL hull. The larger and deeper transom for the case of KCS hull form sometimes can be beneficial at higher Froude number.